2020
DOI: 10.1186/s12879-020-05664-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, phylogeny, and antimicrobial resistance of Escherichia coli pathotypes isolated from children less than 5 years old with community acquired- diarrhea in Upper Egypt

Abstract: Background Diarrhoea, affecting children in developing countries, is mainly caused by diarrheagenic Escherichia coli (DEC). This study principally aimed to determine the prevalence of DEC pathotypes and Extended-spectrum β-lactamase (ESBL) genes isolated from children under 5 years old with diarrhea. Methods A total of 320 diarrhoea stool samples were investigated. E. coli isolates were investigated for genes specific for enterotoxigenic E. coli (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 41 publications
5
34
2
Order By: Relevance
“…These results are higher than reports of previous studies in Egypt, with ESBL prevalence range from 52–69.6%. 16 , 22 , 34 , 35 In the same context as our results, Valverdi et al 36 documented that acute diarrhoea is a frequent reason for intestinal colonization by ESBL producers that reached to 55.5% in acute diarrhoea. This can be explained by the change in the gut flora that occurs in acute diarrhoea, causing predominance of pathogenic bacterial strains.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These results are higher than reports of previous studies in Egypt, with ESBL prevalence range from 52–69.6%. 16 , 22 , 34 , 35 In the same context as our results, Valverdi et al 36 documented that acute diarrhoea is a frequent reason for intestinal colonization by ESBL producers that reached to 55.5% in acute diarrhoea. This can be explained by the change in the gut flora that occurs in acute diarrhoea, causing predominance of pathogenic bacterial strains.…”
Section: Discussionsupporting
confidence: 84%
“… 15 E. coli isolate from a previous study was used as quality control in antimicrobial susceptibility testing. 16 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Brazilian study reported higher rates of antibiotic resistance among typical EPEC strains than among the atypical ones [90]. A major concern nowadays is the emergence of multidrug-resistant strains, which are frequently reported around the globe [11,90,91].…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…Interestingly, ESBL production was determined phenotypically in approximately thirty-seven percent of our isolates. In a similar study, 60.6% frequency of ESBL positive strains have been stated byKhairy et al (2020) in Egypt[16]. In view of the genes encoding ESBLs,Khoshvaght et al (2014) reported a high prevalence of bla TEM and bla CTX−M genes in EAEC isolates (78.9% and 63.1%, respectively)[43] Ali et al (2014).…”
mentioning
confidence: 85%